1979
DOI: 10.1246/bcsj.52.629
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Yahazunol, a New Sesquiterpene-substituted Hydroquinone from the Brown Seaweed Dictyopteris undulata Okamura

Abstract: The structure of yahazunol, an antimicrobial substance isolated from the brown seaweed D. undulata Okamura, was established on the basis of spectral and chemical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Drimane or 4,9-friedodrimane meroterpenoids with a quinone or hydroquinone moiety were frequently isolated from marine sponges [2,3,4,5,6,7,8] and algae [9,10,11]. The same class of compounds having a regular drimane skeleton were also often isolated from both plant-associated [12,13,14,15] and marine-derived [16] fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Drimane or 4,9-friedodrimane meroterpenoids with a quinone or hydroquinone moiety were frequently isolated from marine sponges [2,3,4,5,6,7,8] and algae [9,10,11]. The same class of compounds having a regular drimane skeleton were also often isolated from both plant-associated [12,13,14,15] and marine-derived [16] fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the cyclization between sesquiterpenoid and 3,5-dimethylorsellinic acid (DMOA) units, as well as the rearrangement of DMOA, the type of tetraketide-MSRDs can be further classified into five subgroups (SG I-V), namely citreohybridones , terretonins (148)(149)(150)(151)(152)(153)(154)(155)(156), andibenins (157)(158)(159)(160)(161)(162)(163), autins , and others (194)(195)(196)(197)(198)(199). Isotope labeling experiments revealed that they were all formed through the alkylation of DMOA by FPP as a key step [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Tetraketide-msrds Derived From 35-dimethylorsellinic Acidmentioning
confidence: 99%
“…15) refers to those in which the sesquiterpenoid and DMOA moieties are linked by only one C-C bond. Tropolactones A-D (196)(197)(198)(199) were isolated from the broth extract of a marine-derived fungus of Aspergillus genus. Novofumigatonin (195) was isolated from Aspergillus novofumigatus [143].…”
Section: Tetraketide-msrds Derived From 35-dimethylorsellinic Acidmentioning
confidence: 99%
“…1 The sesquiterpene hydroquinone yahazunol (11), 2 zonarol (12), zonarone (13), isozonarol (14), isozonarone (15), 3 cyclozonarone (16), 4 zonaroic acid and chromazonarol have been obtained from the brown algae Dictyopteris undulata Okamura. 2 The compounds 12-16 and chromazonarol show feeding-deterrent activity against the young abalone Heliotis discus hannai. 4 The sesquiterpene hydroquinones and quinones 12-15, chromazonarol, zonaroic acid and dictyochromenol possess toxicity against killifish.…”
Section: Introductionmentioning
confidence: 99%